BUILDING THE SOCIAL CAPITAL IN RURAL AREASâ€™ SMES WOMEN COOPERATIVE, GARGALIANI, SOUTH-WEST PELOPONNESOS - Papakonstantinidis, Leonidas (FEB - Universitas Lampung, 2018)
The purpose of this paper is to prove that the rationalization of the â€œIntegrated Endogenous Local Developmentâ€ should be proved to be a valuable policy mean, under the proposed methodological procedure of Sensitizing Local People, through the â€œanimation procedureâ€, toward developing their own skills, capacities and therefore their place, that are asked by the local SMEs Sensitization may be proved to be the fundamental methodological tool, for building the social capital at local level, by making valuable local peopleâ€™s â€œintrinsic inclinationsâ€-a â€œtermâ€ which is stronger than â€œcapacitiesâ€- under a new value system, and human communication. â€Sensitizationâ€ - as the upper limit of the sensitization procedure- is been approached, step by step, especially: Establishing the â€œbottom-up approachâ€ in planning the development procedure at local level, Establishing the â€œanimation procedureâ€ among local people, Analysing local people â€œintrinsic inclinationsâ€ in context with a â€œsystem valueâ€, Creating a â€œteam psychologyâ€ among local people, Encouraging local people in finding and adopting the local â€œFlag Themeâ€. The proposed procedure may be useful, especially in small, less developed and isolated rural areas. A case-study â€œWomen Cooperative, Gargaliani, South-West Peloponnesosâ€, is referred as a typical case of the development procedure, based on local people (women) animation in Greece.